2013
DOI: 10.1155/2013/506172
|View full text |Cite
|
Sign up to set email alerts
|

Staging Investigations in Breast Cancer: Collective Opinion of UK Breast Surgeons

Abstract: Introduction. Certain clinicopathological factors are associated with a higher likelihood of distant metastases in primary breast cancer. However, there remains inconsistency in which patients undergo formal staging for distant metastasis and the most appropriate investigation(s). Aims. To identify UK surgeon preferences and practice with regard to staging investigations for distant metastases. Methods. A survey was disseminated to members of the Association of Breast Surgery by e-mail regarding surgeon/breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Clinical or radiological involvement of one or more axillary lymph nodes was the most common indication for a preoperative CT scan. Nearly half of respondents obtained preoperative CT scans for T3 or T4 tumors . In the current study, patients with T4 disease were more likely to undergo RSIS, most commonly prior to neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…Clinical or radiological involvement of one or more axillary lymph nodes was the most common indication for a preoperative CT scan. Nearly half of respondents obtained preoperative CT scans for T3 or T4 tumors . In the current study, patients with T4 disease were more likely to undergo RSIS, most commonly prior to neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…However, improved sensitivity and specificity for axillary ultrasonography in detecting axillary nodal metastases before surgery has increased the number of patients being designated as at least clinical stage IIB and, although the NCCN does not recommend routine staging, it is likely that many of these patients will nevertheless undergo systemic staging owing to patient or physician preference. A 2013 survey revealed that 86 per cent of responding breast surgeons in the UK would perform staging CT in the event of clinical or radiological evidence of nodal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that the likelihood of metastasis is extremely low in asymptomatic early breast cancer, routine use of baseline staging still varies considerably (7). Risk assessment of each tumor stage will Figure 1.…”
Section: Discussionmentioning
confidence: 99%